A MOLECULAR DYNAMICS STUDY OF THE BEHAVIOR OF SODIUM IN LOW ALBITE - Alberti A.; Fois E.; Gamba A. (My University, 2003)
The structural features of albite (atomic coordinates and distances, thermal displacements) at 25 and 1040 'C, obtained by Molecular Dynamic simulations following the Car-Parrinello approach, were favorably compared with those obtained by single-crystal diffraction experiments. Starting from this basis, it was shown that the marked anisotropy of electron density distribution about the positions of the sodium atoms is due to a time average of highly anisotropic thermal vibrations, and not to a space average of multiple positions occupied by Na. Although the large displacement of Na from its center of gravity results in great variations over time of the individual Na-0 distances of the sodium coordination polyhedron, the average distance remains approximately constant, reaching its minimum variation when the 9 nearest 0 atoms are considered, thus supporting a true 9-coordination of sodium.
Keywords: MOLECULES; SODIUM; MINERALOGY; albite